Elastase Mediated Fibrinolysis in Acute Promyelocytic Leukemia - Oudijk, Erik-Jan D.; Nieuwenhuis, H. Karel; Bos, Rogier; Fijnheer, Rob (Thrombosis and Haemostasis, 2000)
The bleeding syndrome of acute promyelocytic leukemia (APL) is complex and consists of disseminated intravascular coagulation (DIC) and hyperfibrinolysis. Elastase, derived from malignant promyelocytes, is believed to mediate the fibrinogeno- and fibrinolysis by aspecific proteolysis. In this study we measured the role of elastase in fifteen patients with APL by using an assay for elastase degraded fibrin(ogen) and the results were compared with those obtained in patients with sepsis induced DIC.High levels of elastase were observed in sepsis and APL. The levels of fibrinogen and fibrin degradation products were significantly higher in APL patients compared to patients with sepsis induced DIC. Nevertheless, the level of elastase degraded fibrin(ogen) was higher in the sepsis group (635.3 ng/ml, compared to 144.3 ng/ml in APL; p <0.0001). So, the enormous increase in fibrin and fibrinogen degradation products in APL cannot be explained by elastase activity. This study suggests a minor role for elastase mediated proteolysis in the hemorrhagic diathesis in APL patients.
Keywords: Acute promyelocytic leukemia; fibrinolysis; coagulation; sepsis; elastase